An Analysis of Basic Interaction, Communication, Team Building, and Problem-solving Skills of Primary School Students in Marching Band Activities - Altaftazani, Deden Herdiana; Rahayu, Galih Dani Septiyan; Kelana, Jajang Bayu (Mimbar Sekolah Dasar, 2020)
This research is motivated by the importance of social skills for elementary school students. Social skills are abilities that must be possessed by every individual to function well in their social environment. Social skills must be instilled through the stages of learning and habituation. One of the approaches to instill social skills is through marching band activities. This research aimed at finding out how marching band activities can emerge and develop students' social skills. This research used a qualitative approach with a case study research design. Three ways of collecting data were used to obtain data, which are interviews, observation, and documentation. As a result, marching band activities can bring up various social skills of students, including basic interaction skill, basic communication skill, team or group building skill, and problem-solving skill. Meanwhile, the factors that influenced the formation of social skills in marching band activities in elementary schools are group activity factor, situation factor, regulatory factor, program or design factor, and peer relationship factor.